Isu-Isu Kontemporer dan Solusi Pengembangan Perbankan Syariah - Rangkuti, Ayub; Y, Yudi; S, Syahpawi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The existence of Islamic banks in Indonesia was established to avoid the issue of interest which continues to be a long debate which is feared to contain elements of usury. Therefore, every Sharia banking activity must be protected from usury. Efforts to avoid these concerns include implementing profit sharing. The Muslim community's understanding of sharia banking is still limited to routine religious activities, even though sharia banking covers all aspects of life. It is time to change this perspective or issues and how to increase Sharia financial literacy among the community in order to expand access and use of Sharia banking services. In this paper, the author uses a qualitative descriptive method to look at issues related to sharia banking. The data source in this research is library data where the author collects writings, books, journals related to the main issue of the study. In data analysis, the author uses qualitative analysis methods starting with data coding, data reduction, and drawing conclusions. From the analysis of the discussion or explanation it was found that it was in accordance with this paper. that efforts to develop the existence of sharia banking are a very important orientation considering that its existence is the 'life' and 'soul' of the Muslim community in order to help alleviate community poverty which is mostly experienced by Muslims. There are a number of problems as well as solutions for the development of sharia banking so that it can run optimally, aspects of commitment to implementation, aspects of human resources, and sharia banking marketing strategies to innovate products according to community needs.